Analisis Pemilihan Metode Penyusutan Aset Tetap - Trudy Maryona Nussy (Jurnal Administrasi Terapan, 2026)
This study aims to determine depreciation values of fixed assets and to compare two depreciation methods, namely straight-line and declining balance methods. The findings show that depreciation expenses calculated using the straight-line method are higher than those calculated using the declining balance method during the 2023–2025 period. Differences in depreciation expenses between the two methods amounted to IDR 3,314,291 in 2023, IDR 9,449,260 in 2024, and IDR 19,768,402 in 2025.Keywords: Depreciation, Straight-Line Method, Declining Balance Method